1989
DOI: 10.1038/jcbfm.1989.94
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bilirubin on Cerebral Arterial Tone in vitro

Abstract: Hemoglobin and its metabolite, bilirubin, have been shown to be present in high concentrations in CSF following subarachnoid hemorrhage (SAH). Several reports have indicated that hemoglobin is a potent cerebral vasoconstrictor and therefore is considered to be an active principle in the genesis of cerebral vasospasm. The possible role of bilirubin on the genesis of cerebral vasospasm, however, has not been clarified. The effect of bilirubin on cerebral vessel tone was therefore examined using in vitro tissue b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 37 publications
3
14
0
Order By: Relevance
“…Furthermore, the cerebral arterial smooth muscle of the large arteries at the base of the pig brain, which has been shown to contain mainly b1-adrenoceptors with fewer b 2-adrenoceptors and not significant a-adrenoceptors, relaxes exclusively upon application of exogenous NE (4,12,13). TNS of these isolated cerebral arteries exclusively elicited neurogenic vasodilation, a result similar to that found in the large cerebral arterial smooth muscle of the cat, which contains mainly a-adrenoceptors (1,14). This tetrodotoxin-sensitive vasodilation in large cerebral arteries of the pig and cat elicited by TNS was not affected by propranolol or guanethidine (1,4,12).…”
Section: Sympathetic Adrenergic Innervation In the Cerebral Circulationsupporting
confidence: 58%
See 1 more Smart Citation
“…Furthermore, the cerebral arterial smooth muscle of the large arteries at the base of the pig brain, which has been shown to contain mainly b1-adrenoceptors with fewer b 2-adrenoceptors and not significant a-adrenoceptors, relaxes exclusively upon application of exogenous NE (4,12,13). TNS of these isolated cerebral arteries exclusively elicited neurogenic vasodilation, a result similar to that found in the large cerebral arterial smooth muscle of the cat, which contains mainly a-adrenoceptors (1,14). This tetrodotoxin-sensitive vasodilation in large cerebral arteries of the pig and cat elicited by TNS was not affected by propranolol or guanethidine (1,4,12).…”
Section: Sympathetic Adrenergic Innervation In the Cerebral Circulationsupporting
confidence: 58%
“…Similar results were found in isolated large cerebral arteries at the base of the cat brain that nicotine-induced vasodilation was sensitive to L-NNA (33). In these cerebral arteries of the cat, postsynaptic a-adrenoceptors are predominant, and exogenous NE induces a constriction exclusively (14,36). These findings clearly indicate that nicotine-induced vasodilation in the cat cerebral arteries can not be due to a direct effect of NE on the postsynaptic smooth muscle cells.…”
Section: Nicotine-induced No-mediated Cerebral Neurogenic Vasodilatiomentioning
confidence: 64%
“…We have also suggested that bilirubin oxidation products, BOXes (Kranc et al, 2000) were found in the CSF of SAH patients and that these BOXes might contribute to vasospasm (Clark et al, 2002;Lyons et al, 2004). There are independent reports suggesting that oxidative stress (Cook, 1995;Macdonald and Weir, 1994;Watanabe et al, 1988;Weir, 1995) and bilirubin (Jia-Pei Miao and Jer-Fu Lee, 1989;Page et al, 1994) may correlate or contribute to vasospasm based on measurements in CSF (Page et al, 1994). But the thesis that oxidative stress leading to the oxidation of bilirubin (resulting in BOXes formation) as a contributing factor for vasospasm has been little studied.…”
Section: Discussionmentioning
confidence: 99%
“…Bilirubin levels rise in the spinal fluid following subarachnoid haemorrhage [31] and their time course correlates well with the accepted time course of cerebral vasospasm, but bilirubin is not vasoactive. Thus there has been an interest in bilirubin's association with vasospasm, though with mixed results [3,4,8,9,27,28,30,32,38,47]. A bilirubin derivative such as BOXes is therefore quite consistent with the clinical characteristics of vasospasm.…”
Section: Discussionmentioning
confidence: 99%